Heart Rate Measurement during Stereotyped Motor Behavior in Autism Spectrum Disorder - HEALY, OLIVE; LYDON, SINEAD MARY (Springer, 2015)
Previous research has suggested that a relationship may exist between physiological arousal and engagement in motor stereotypy among children and adolescents with autism. It has been speculated that levels or alterations of physiological arousal may act as antecedents or reinforcing consequences for stereotypy. The current study sought to investigate the relationship between these two variables among five children aged between four and 17 years who were diagnosed with autism spectrum disorder. The results revealed little association between physiological arousal and stereotypy among these participants. However, a consistently atypical physiological response to stress, suggestive of physiological blunting, was observed. The implications of these findings for our understanding of the function of stereotypy, and stress responsivity among persons with autism, are discussed along with suggestions for future research.
PUBLISHED
Keywords: autism; heart rate; physiological; stereotypy; blunting; stress